Missionary Travels and Adventures in Africa - London Missionary Society (London)
The life of David Livingstone - with brief account of the commencement of the mission at UJIJI where Stanley found Livingstone
Keywords: "MISSIONARIES, CHRISTIAN - BIOGRAPHY;DAVID LIVINGSTONE 1813 - 1873;MISSIONS - AFRICA;AFRICA - DESCRIPTION AND TRAVEL"